2013
DOI: 10.1097/pas.0b013e31826cb1d1
|View full text |Cite
|
Sign up to set email alerts
|

Plasmablastic Transformation of Low-grade B-cell Lymphomas

Abstract: Histologic transformation of low-grade B-cell lymphoma to diffuse large B-cell lymphoma is associated with poor prognosis. Although plasma cell differentiation is common in these lymphomas, an overt plasmablastic transformation (PBL-T) has been only rarely reported. We report 6 cases of PBL-T occurring in 3 chronic lymphocytic leukemias (CLL) and 3 follicular lymphomas. Five patients were men, and the mean age was 65 years (range, 52 to 72 y). None of them had history of immunodeficiency. In 3 cases the PBL-T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 47 publications
(46 reference statements)
0
53
0
Order By: Relevance
“…Most patients who develop RS-PBL are men, 52-77 years of age. A serum or urine paraprotein can be detected in some patients [18]. In addition to typical plasmablastic features, residual CLL/SLL cells may be identified in some areas.…”
Section: Plasmablastic Lymphomamentioning
confidence: 95%
See 4 more Smart Citations
“…Most patients who develop RS-PBL are men, 52-77 years of age. A serum or urine paraprotein can be detected in some patients [18]. In addition to typical plasmablastic features, residual CLL/SLL cells may be identified in some areas.…”
Section: Plasmablastic Lymphomamentioning
confidence: 95%
“…CD5, CD20, PAX5, and IRF8 are commonly negative. Molecular studies have shown monoclonal IGH [18] and MYC rearrangement [47]. The prognosis of patients with RS-PBL is grim.…”
Section: Plasmablastic Lymphomamentioning
confidence: 99%
See 3 more Smart Citations